(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
The Pb–Zn (lead–zinc) sulphide mineralization within the Benue Trough extends from the Lower Benue to the Upper Benue Trough, indicating a widespread metallogenic belt. Representative ore samples from this region were examined using Scanning Electron Microscopy (SEM) to investigate their mineralogical and petrographic characteristics. Petrographic analysis reveals that the mineralization is predominantly composed of Galena (PbS) and Quartz (SiO₂), with minor occurrences of Chalcopyrite (CuFeS₂), Magnetite (Fe₃O₄), and trace aluminosilicate minerals. During later stages, under near-surface and oxidizing conditions, significant replacement processes occurred. Galena was partially replaced by Anglesite (PbSO₄), while associated copper-bearing minerals underwent alteration. The movement of copper-rich solutions through the deposit led to the formation of thin, persistent bands of Covellite (CuS), often found within or adjacent to Anglesite zones. These formed contemporaneously with the oxidation of Galena. Chalcopyrite was similarly affected by oxidation, transforming into Covellite, whereas Magnetite and Pyrite (FeS₂), where present, remained largely unaltered, suggesting their relative resistance to oxidative weathering. Backscattered SEM imaging identified two distinct types of Galena: altered and unaltered. Further petrographic analysis in polished sections revealed three main textural varieties of Galena: cubic, fibrous (or gneissic), and granular. These textures provide insights into the paragenesis and post-depositional alteration history of the Pb–Zn mineralization in the Benue Trough.